Implementasi Media Pembelajaran Berbasis Android dan Moodle Untuk Meningkatkan Kompetensi Belajar Siswa Pada Mata Pelajaran Desain Multimedia Interaktif - Aisyathus Gading Setiati; I Gusti Lanang Putra Eka Prismana (IT-Edu : Jurnal Information Technology and Education, 2026)
In Vocational High Schools (SMK), digital transformation is highly needed to support the development of adaptive and contextual learning media. The aim of this study is to explore the development process and implementation of digital learning media based on Android and Moodle, in order to support the improvement of students' competencies in Interactive Multimedia Design learning. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was applied as a framework for developing and implementing the technology-based learning media within the scope of the Research and Development (R&D) method. The study was conducted with a total of 36 students from Grade XII DKV at SMK Negeri Gudo, who were divided into two groups: an experimental class and a control class. The learning media was developed by integrating Moodle as a Learning Management System (LMS) and Figma as a UI design project tool within a Project-Based Learning (PjBL) approach. The media was designed to be responsive, allowing it to be accessed via Android devices without requiring additional application installation. Expert validation results indicated a high level of feasibility, with a score of 82.5%. The effectiveness test through pretest-posttest data analysis showed a significant improvement in student competencies. The average posttest score in the experimental class reached 80.00, which was considerably higher than the control class average of 55.00. This result was statistically significant, with a significance value of 0.000, which is below the threshold of < 0.05. Therefore, this media is proven effective in enhancing students' understanding and skills in UI design in an applicable, collaborative, and flexible manner through Android devices. Keyword : Learning media, Moodle, Android, Project-Based Learning, UI design.